Hubungan antara Nilai dan Resiliensi Keluarga yang Kedua Orang Tuanya telah Meninggal Dunia - Wilda Ayuni Septiawati; Sugiarti A. Musabiq (Fakultas Psikologi Universitas Pancasila, 2011)
This study aims to observe values and family resilience, and their correlation in families with deceased parents. This study uses a quantitative approach with non-experimental research design (field study) and involves 42 respondents. The result shows that most of the respondents hold high values and are at high resilience level. In addition, this study also reveals a correlation between values of achievement, security, and spirituality and family resilience in families with deceased parents.